Il Quartiere degli Artigiani a Calvatone (Milano University Press, 2024)
The volume presents the outcomes of a research project directed by Maria Teresa Grassi on the vicus of Calvatone-Bedriacum. From 2005 to 2013, the University of Milan investigated a sector of the Roman settlement, revealing the remains of a production complex situated between two residential areas. The chapters show the primary excavation evidence and highlight the most significant contexts and classes of materials for reconstructing the life and abandonment of a bakery from the 1st century AD. This is situated within the broader framework of the urban planning of the vicus and the population of the Cisalpine Gaul.